Assessing the efficiency of microplastics extraction methods for tropical beach sediments and matrix preparation for experimental controls - Bonita, Jan Danielle P.; Gomez, Norchel Corcia F.; Onda, Deo Florence L. (Frontiers in Marine Science, 2023)
Microplastic pollution has become a global issue, eliciting attention not just from the scientific community but also both from the public and governmental bodies. Drawing data-driven policies and interventions, however, remain difficult due to the severely lacking baseline information from different environments such as beaches. One of the challenges in doing baseline studies is the lack of harmonized methodologies that will allow for comparison of results, integration of data, and its effective translation to evidence-based policies. Emphasis on quality control measures among baselining efforts through the proper implementation of experimental controls is also lacking. To address these gaps, we compared methodologies for preparing the sediment matrix for experimental controls, as well as evaluated protocols for extracting microplastics from tropical beach sediments. Beach sediments were collected, dried, sieved, and spiked with known amounts of microplastics of different polymer types. The removal and extraction efficiencies of the protocols being compared were evaluated. Our results showed that subjecting beach sediments to a furnace at 550° C for 4 hours is the most efficient way to remove plastic contamination, implying its applicability for preparing experimental controls. Meanwhile, a modified version of Masura et al. (2015), one of the widely cited methodologies for microplastics extraction, exhibited the highest mean extraction efficiency (99.05 ± 0.82%) among the protocols being compared. Results of this work will be useful in identifying methods that can be adopted and utilized for research and baselining efforts not just in the Philippines but also in Southeast Asia. This will also be helpful in the harmonization of methods, data reporting, and even skills as implemented through the regional and national action plans to address marine plastic pollution.